The Anisotropic Mechanical and Tribological Behaviors of Additively Manufactured (Material Extrusion) Implant-Grade Polyether Ether Ketone (PEEK) - Mohammad Reza Maydanshahi; Mohammad Reza Najari; Tom Slatter; Mahdi Mohammadpour (Lubricants, 2024)
In this study, we investigated the mechanical and tribological properties of the layer-by-layer structure of additively manufactured implant-grade Polyether Ether Ketone (PEEK) through the Material Extrusion (ME) process as a potential substitute for artificial joints. The effective elasticity modulus of the anisotropic 3D-printed PEEK was determined to be 2.505 GPa along the vertical and horizontal build orientations. The lubricated friction and wear performance were assessed using a pin-on-disk test under various loads, including 14, 30, 50, and 70 N, with a sliding speed of 50 mm/s over a total distance of 1 km at 37 °C. The contact parameters between the hemispherical steel pin and 3D-printed PEEK disks, involving contact pressures over the circle of contact, were observed to increase as the load increased. The results indicated that the wear coefficient exhibited a rise from <semantics>1.418 × 10−5</semantics> to <semantics>2.089 × 10−1<mtext> </mtext></semantics> as the applied loads increased, signaling a shift from mild to severe wear regimes. Fetal Bovine Serum (FBS) as a lubricant exhibited a mixed mechanism, ascertained through the Stribeck curve, as well as a minimum fluid film thickness of 1.346 nm under an isoviscous–elastic regime, as calculated by the maximum load. Moreover, the mechanism governing wear during sliding, influenced by both normal axial and shear loads, primarily involved adhesion.